Determination of Essential Mineral Concentrations in Some Turkish Teas and the Effect of Lemon Addition - Derun, Emek Moroydor (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2014)
Essential elemental concentrations of Turkish black, green, and earl grey tea infusions were determined with and without added lemon. Daily percentage elemental intake values from these 3 teas with and without lemon addition were calculated based on Recommended Dietary Allowances (RDA). Calcium (Ca), cobalt (Co), copper (Cu), iron (Fe), potassium (K), magnesium (Mg), sodium (Na), selenium (Se), and zinc (Zn) concentrations were increased after lemon addition. The chromium (Cr) concentration was decreased in green and earl grey teas and increased in black tea after lemon addition. The manganese (Mn) concentration was increased in green tea and decreased in black and earl grey teas after lemon addition. The phosphorus (P) concentration was increased in earl grey and green teas, and decreased in black tea after lemon addition. The daily intake value of Mn was found above the RDA value.
Keywords: tea; black; earl grey; green; lemon; BLACK TEA; INFUSIONS; METALS; PLANT; Food Science & Technology